China contributes to the ISID in Pacific Island Countries - Yue, Hongfei (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
As we know, the Small Island Developing States face special challenges to their development. This is particularly true for the Pacific Island States, scattered as they are over a huge area of ocean. More specifically, the 22 Pacific Island countries are scattered over one third of the globe (thirty million sq. km. mostly ocean). The total population of the South Pacific excluding Australia and New Zealand is about 8 million; half of which reside in Papua New Guinea.Many stakeholders have been involving in assisting the development of Pacific Island Countries for a long time. In recent years, China has become one of the active players in the inclusive and sustainable development of Pacific Island Countries.